The Algebraic and Geometric Classification of Compatible Pre-Lie Algebras - Abdelwahab, Hani; Kaygorodov, Ivan; Makhlouf, Abdenacer (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
In this paper, we develop a method to obtain the algebraic classification of compatible pre-Lie algebras from the classification of pre-Lie algebras of the same dimension. We use this method to obtain the algebraic classification of complex 2-dimensional compatible pre-Lie algebras. As a byproduct, we obtain the classification of complex 2-dimensional compatible commutative associative, compatible associative, and compatible Novikov algebras. In addition, we consider the geometric classification of varieties of cited algebras, that is, the description of their irreducible components.